Neurovirulence variation among the two genotypes of Chikungunya virus in Malaysia / Chiam Chun Wei - Chiam , Chun Wei (2015)
Chikungunya virus (CHIKV), an alphavirus of the family Togaviridae, causes fever, polyarthritis, and rash. There are three genotypes: West African, Asian, and East, Central and South African (ECSA). The latter two genotypes have caused outbreaks in Malaysia. Recent ECSA CHIKV outbreaks have been associated with severe neurological disease including encephalitis, meningitis, and acute flaccid paralysis. It is not known if different CHIKV genotypes are associated with different severity of neurological disease. In this study, the neurovirulence of Asian (MY/06/37348) and ECSA (MY/08/065) strains of CHIKV were compared by intracerebral inoculation in suckling mice, followed by virus titration, quantitative real-time PCR, histopathology, and gene expression analysis of the harvested brains. Both genotypes of CHIKV replicated similarly in the brains, yet suckling mice infected with Asian CHIKV showed higher mortality compared to ECSA CHIKV-infected mice and control mice. Histopathologic analysis showed that both CHIKV genotypes were found to spread within the brain (where CHIKV antigen was localised to astrocytes and neurons) and beyond to skeletal muscle. In Asian CHIKV-infected suckling mice, apoptosis and necrosis were observed earlier in brains, and more extensive CHIKV spread and pathologic changes were seen in skeletal muscle. Gene expression analysis showed that pro-apoptotic genes (eIF2αK2) were upregulated at higher levels in Asian CHIKVinfected suckling mice, while genes involved in anti-apoptosis (BIRC3) and antiviral responses and CNS protection (CD40, IL-10RA, MyD88, and PYCARD) were upregulated more highly in ECSA CHIKV-infected suckling mice. In conclusion, these findings suggest that the higher mortality observed following Asian CHIKV infection in mice is not due to higher viral replication in the brain as there was more spread in muscle and due to differentially expressed genes involved in antiviral activity and CNS iv protection. Further studies could focus on the differences in viral sequences encoding neurovirulence determinants. This information on important host responses may be used for development of therapeutic and prophylactic strategies against CHIKV infection, and identification of biomarkers for neurological CHIKV infections